Digital Employer Branding for Enabling Gen Y in the ITeS Sector in Eastern India - Patra, Gouranga; Mukhopadhyay, Indranil; Dash, Chinmaya Kumar (Prabandhan: Indian Journal of Management, 2019)
Employer brand is the image of the organization as an employer. Employer’s value propositions (EVP) communicate that image to the existing as well as potential employees. It reinforces why talented people would like to join and stay with an organization. Today, the nature of work is confronted with many challenges for staffing knowledge-based high performance work places (e.g. IT enabled services), with greater demands on employee competencies, diverse workforce, and growing global shortfalls of talented applicants. In today’s digital economy, where the modern business world (Known as Business 4.0) is shaped and reshaped by digital five forces such as social media, mobile (including gamification) analytics, cloud computing, and robotic automation at the workplace, these digital platforms bring a sweeping change by helping re-imagine how the 21st century business processes operate and interact with their different stakeholders, especially with their customers and employees. The purpose of this paper was to examine how in today’s economy such forces of the digital world play the role for continuous promotion of strong employer branding for attracting, motivating, and retaining top talents for ensuring continued high performance. This study focused on the ITeS sector in Eastern India. The thoughts of Gen Y graduates and post graduates were analyzed by the help of primary data obtained through a random sample survey conducted between November 2017 to May 2018 as to have deeper insights into application of various ingredients of employer branding and their underlying theme for effectiveness in the global ITeS organizations.